PONDOK PESANTREN AS'ADIYAH - Muhammad As'ad (Balai Penelitian dan Pengembangan Agama Makassar, 2009)
This article is the summary of research on the oldest boarding school inSouth Sulawesi : As 'adiyah. It aims to describe its religious view, lecture,learning system, networks and relation with society.Result shows that As'adiyah boarding school embraces Ahlusunnahwal Jamaah based on Imam Syafi' teachings. It can be categorized, as